BIOWISATA MELALUI VIRTUAL REALITY PADA PEMBELAJARAN BIOLOGI DI KURIKULUM MERDEKA - Handayani, Asih; Khoirumufida, Fidiya; Nashiroh, Wafiq; Zulfa, Triana Atika (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
In the current era, technology is developing rapidly. Technology is used in relation to media to convey information and can help build students' knowledge. Technology in learning can be utilised by applying Virtual Reality (VR) technology. One of them is Virtual Biotourism via VR in Biology learning. Virtual tourism can be used in independent curriculum learning as an idea for teachers to present and deliver lessons that will attract more students' interest in participating in learning and improve the quality of learning. The aim of preparing this article is to discover the application of VR in biology learning in the digital era and the application of Virtual Biotourism through VR in Biology learning. This research uses the Literature Review method by collecting and analysing data from several existing research journal sources. The research results are the result of an analysis of 4 research journals regarding the use of VR. From the results of the analysis, virtual reality technology is effectively applied in biology learning in this digital era because it can help teachers provide visualisations or descriptions of the material presented in the learning process so that students can understand it more easily.